BUSANA PANGGUNG DITINJAU DARI TATA RIAS KARAKTER DAN TATA RIAS FANTASI - -, Marwiyah (Teknobuga, 2010)
Cloth Podium as one of the means, media of penggembang and oftransformasi materialization an culture, arrange character make up and arrange fantasymake up have role which strategic enough. That thing is enabled by because arrangingcharacter make up and arrange fantasy make up represent materialization of total swansong, atara arrange face make up, arrangement of cloth, settlement of hair and alsoused accessories there is in one unity of concept. In designing podium cloth to arrangecharacter rias and arrange fantasy rias, usage of element cover: line, direction, sizemeasure, form, bold dark value, and colour of tekstur, and also ground cover:compatibility, comparison, balance, cynosure and rhythm have to always there is, strivedin making to be designed by podium cloth according to figure character and idea sourcemade by as beautiful as possible with high innovation and creativity will be yielded bynew cloth masterpiece, beautiful, harmonious and elegen.Keywords: Cloth Podium, character make up, fantasy make upÃÂ Busana panggung sebagai salah satu wahana, media penggembang dantransformasi perwujudan suatu budaya, tata rias karakter dan tata rias fantasi memilikiperanan yang cukup strategis. Hal itu dimungkinkan karena tata rias karakter dan tatarias fantasi merupakan perwujudan karya seni yang total, atara tata rias wajah,pengaturan busana, penataan rambut serta asesoris yang digunakan ada dalam satukesatuan konsep. Dalam merancang busana panggung untuk tata rias karakter dan tatarias fantasi, penggunaan unsur meliputi: garis, arah, ukuran, bentuk, nilai gelap terang,warna dan tekstur, serta asas meliputi: keselarasan, perbandingan, keseimbangan,irama dan pusat perhatian harus selalu ada, diupayakan dalam membuat desain busanapanggung sesuai watak tokoh dan sumber ide dibuat seindah mungkin dengankreatifitas dan inovasi yang tinggi akan dihasilkan karya busana baru, indah, harmonisdan elegen.Kata Kunci: Busana panggung, tata rias karakter dan tata rias fantasi